Preparing New Principals in Developing countries: Selection and Induction (Sotang, Yearly Peer Reviewed Journal, 2019)
Purpose: This paper aims to overview of the challenges facing new principals in developing country and to explore the provision for leadership and management development for new and experienced school leaders.Design/methodology/approach: Based on recent research and literature, the paper analyses the experience of principals and proposes an induction model for principalship in developing countries.Paper type: Literature reviewFindings: School principals in developing country face a daunting challenge. They often work in poorly equipped buildings with inadequately trained staff. There is rarely any formal leadership training and principals are appointed on the basis of their teaching record rather than their leadership potential. Induction and support are usually limited.Originality/value: The paper provides an overview of the limited literature and research on new principals in developing country and develops a grounded conceptualisation of their role.